2003
DOI: 10.2527/2003.813641x
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in the growth hormone and growth hormone receptor genes with blood serum insulin-like growth factor I concentration and growth traits in Angus cattle1,2,3

Abstract: This study was conducted to identify polymorphisms in the promoter and coding regions of the bovine growth hormone and growth hormone receptor genes and to study association of polymorphisms identified in these genes with growth traits and serum insulin-like growth factor-I (IGF-I) concentration. The denaturing gradient gel electrophoresis method and sequencing were utilized to identify three new single nucleotide polymorphisms in the promoter region of the growth hormone gene in Angus cattle. Polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
1
29

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 29 publications
1
98
1
29
Order By: Relevance
“…Only one SNP was identified in a non coding region (intron 1) in position AJ575419:g.419C>T. It is noteworthy to state that numerous mutations in this gene were documented in other species, viz. in cattle more than 10 SNPs have been recorded (Chikuni et al, 1994;Ge et al, 2003;Musa, 2007). Also, many SNPs have been reported in sheep (Bastos et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one SNP was identified in a non coding region (intron 1) in position AJ575419:g.419C>T. It is noteworthy to state that numerous mutations in this gene were documented in other species, viz. in cattle more than 10 SNPs have been recorded (Chikuni et al, 1994;Ge et al, 2003;Musa, 2007). Also, many SNPs have been reported in sheep (Bastos et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Association of several polymorphic sites (SNPs) in different candidate genes with economic traits has been much investigated in different animal species. Work based on characterization of candidate genes and their association with animal performance in camels is meagre compared with cattle (Lucy et al, 1991;Schlee et al, 1994;Ge et al, 2003), sheep (Wallis et al, 1998;Bastos et al, 2001) or goats (Wallis et al, 1998;Neelam Gupta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Teniendo en cuenta lo anterior, se debe tener en cuenta que para el desarrollo de un programa de selección asistido por marcadores moleculares, es pertinente realizar la evaluación a nivel local sobre el genotipo más deseado por su relación con parámetros productivos, debido a que los reportes son ambiguos (9,14,24) y pueden ser variables de acuerdo al lugar donde son evaluados y a la raza de los animales (24). Además, en Colombia no se han reportado asociaciones significativas entre el alelo MspI posiblemente porque la única investigación llevada a cabo por Echeverri et al (22), no poseía un numero de animales que permita lograr la significancia deseada.…”
Section: Figuraunclassified
“…Actualmente se conocen múltiples polimorfismos al interior del gen o en regiones reguladoras (9). Una de estas variantes reportadas corresponde a un sitio que puede ser reconocido por la endonucleasa de restricción MspI (10), el cual fue localizado como un polimorfismo en el intrón 3 en la posición 1547, que se debe a la transición de Timina, T a Citosina, C (11).…”
Section: Introductionunclassified
“…There are several distinct 5 untranslated region (exon 1) variants in mouse (L1-L5) as well as human GHR (V1-V9), and expression of each transcript is regulated by a different promoter (Edens & Talamantes 1998, Menon et al 2001. Several polymorphisms in the promoter region of GHR gene were reported in species including humans (Hadjiyannakis et al 2001), Angus steers (Hale et al 2000) and Angus cattle (Ge et al 2003), although hitherto there has been no report in mice. Interestingly, the polymorphisms in humans located at 87 bp upstream of V9 (Hadjiyannakis et al 2001), homologous to mouse L3, correspond to those we found in mice.…”
Section: Figurementioning
confidence: 99%